Tradisi Pengajian Lapanan dalam Atifitas Sosial Masyarakat - Bahrun Ali Murtopo (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
Lapanan Study in Religious Values. The emergence of the Lapanan Koran today is an interesting phenomenon. Lapanan recitation was born at the same time as the complexity of the problems faced in society, such as theft, drugs, promiscuity and so on. Therefore, starting from public awareness to stem this problem through understanding and increasing religious values ​​is absolutely necessary. Lapanan Recitation is not just a religious activity that prioritizes ritualistic aspects, furthermore Lapanan Recitation is self-improvement as an educational process, which teaches and plays a role in instilling religious values ​​in society as a spiritual spiritual addition. Aqidah about faith which includes the five pillars of Faith, morals or behavior such as greeting when visiting and respecting people. in instilling religious values ​​for the community is to play the role of creator (the first to start or initiate), facilitator (who provides), and educator (education). make field study activities for the community and youth so that youth in the village are more active in religious, social and cultural activities which are good for increasing or maximizing the role of the community in the social life of the community.